Correlation Between Emotional Intelligence and Problem Solving Skill of Health Students of Faculty of Medicine Universitas Hasanuddin - Hasnah Hasnah; Desy Ana Hendra; Hapsah Hapsah (Faculty of Nursing, Universitas Hasanuddin, 2018)
Background: High demands in all conditions require proffesional health workers. In dealing with patients, health workers need high emotional intelligence and problem solving skills that are qualified to deal with various problems. Objective: To analyze correlation between emotional intelligence with problem solving skill of health student of Faculty of Medicine Universitas Hasanuddin. Method: This quantitative research was conducted in August-September 2017, using observational study design with cross sectional analytic approach. Population in this research is health students Faculty of Medicine Universitas Hasanuddin who forced in 2013, 2014, 2015, 2016 (N=1995). Sampling technique using cluster random sampling (n=333). The data were analyzed with Spearman’s Rho test. Results: More than half of respondents had a low emotional intelligence (58.3%) and medium level of problem solving skill (51,4%). Correlation coefficient both of them is weak (r=0,222; p value = 0.000 <0,05). Conclusion: There is a weak correlation between emotional intelligence with problem solving skill of health student of Faculty of Medicine Hasanuddin University. The higher the emotional intelligence of the student, the higher the level of problem solving skill.